The Category Types of Extensions of a Tambara-Yamagami Category (Journal of Mathematical Study, 2024)
In this paper, we study the group extension of a Tambara-Yamagami category which has Frobenius-Perron dimension $2pq,$ where $p,q$ are prime numbers. Weprove that there are two possible category types when $p e q,$ and five possible categorytypes when $p=q.$
Keywords: Fusion category; extension; Tambara-Yamagami category; category type.